Diagnóstico de las etapas del ciclo Estral mediante citología vaginal de las hembras caninas que llegan al Hospital Docente Veterinario César Augusto Guerrero durante el periodo septiembre diciembre del 2014 - Mochas Japón, Vania Cecibel (2015)
In this thesis project "DIAGNOSIS cycle stages ESTRAL Pap BY FEMALES DOGS REACHING THE VETERINARY TEACHING HOSPITAL" AUGUSTO CESAR GUERRERO "DURING DECEMBER SEPTEMBER 2014" 65 samples were evaluated and two types were used stains for the diagnosis of the stages of the estrous cycle: Diff Quik and Giemsa, 65 dogs demonstrated that 32.31% of 100% of the samples yielded income of basal and parabasal cells Also the 63.08 % they had intermediate cells representing 81.84% of the samples tested surface cells. And 72.31% of enucleated cells. In the stages of the estrous cycle it was determined that 21.54% were crossing Proestrus stage. 46.15% were in the next stage Estro, Also the 13.85% in the Right stage, and 18.46% in Anestrus. According to the type of race it is demonstrated 64.6% of mixed race were in the stages of proestrus, estrus, Right and Anestrus, 20% corresponding to the Bulldog breed was found in the stages of proestrus, estrus and Right , with 6.2% in the Pitbull breed Proestrus stages and Estro they were found. Also with 3.1% the Pekingese breed found in the stages of proestrus and estrus, 3.1% the Basset Hound breed was found in the stages of proestrus and estrus. 3.1% finally the French Poodle breed found in the stages of estrus and anoestrus. According to the variable age, 55.4% were of young age, 40.0% were in adulthood and 4.6% were from the senile age. In differentiating staining with Diff-Quik staining throws us a result of 100% of clarity in the microscopic view for analyzing estra cycle stages, l with Giemsa stains were the same result was obtained that was found with Diff-Quik staining, but with a microscopic clearly visible not 100%, as a result of the sample for 14 consecutive days have, the Twelfth day we observed a 10% superficial cells, 90% of anucledas cells, amount accurate and sufficient female cells need to perform artificial insemination.